Teaching colleagues how to discuss prognosis as part of a hospital-wide quality improvement project : the positive impact of a 90-minute workshop - Jacobsen, Juliet; Whitlock, Sandra N; Lee, Hang; Lindvall, Charlotta; Jackson, Vicki (Journal of Pain and Symptom Management, 2015)
BACKGROUND: Many physicians have difficulty with discussions about prognosis. The aims of this study were to evaluate why physicians struggle to discuss prognosis and to measure the effect of a 90-minute communication workshop on self-reported skill. MEASURES: An evaluation study was used with three measurement points: before the 90-minute communication workshop (e-mail survey); immediately after the workshop (paper survey); and one month after the workshop (e-mail survey). INTERVENTION: Physicians from diverse specialties at a single academic institution were paid to participate in a 90-minute communication workshop on discussing prognosis. OUTCOMES: Physicians identified several reasons why discussions of prognosis are hard: "I am not sure of the actual prognosis" (58.9%; 95% CI, 50.9, 66.5), "I worry I will take away hope (42.9%; 95% CI, 35.2, 50.9), and "I worry the patient is not ready to hear the information" (42.9%; 95% CI, 35.2, 50.9). Physicians who attended this short workshop reported that they could apply what was learned to their work immediately (4.6, range 1-5). One month after the workshop, 91% of respondents reported trying a skill learned in the workshop. The most frequently used skill was Ask/Tell/Ask (61.5%; 95% CI, 51.6, 70.6). CONCLUSIONS/LESSONS LEARNED: A short workshop on discussing prognosis was highly valued by physicians from diverse specialties and a majority reported using at least one of the communication skills learned.
Copyright © 2015 American Academy of Hospice and Palliative Medicine. Published by Elsevier Inc. All rights reserved.
Keywords: Boston; Curriculum; Education/organization & administration; Education, Medical, Continuing/organization & administration; Hospital Administration/methods; Informed Consent; Patient Education as Topic/organization & administration; Physician-Patient Relations; Prognosis; Quality Improvement